Religiosity of pharmacy students of UIN Malang during COVID-19 pandemic - Ach. Syahrir; Abdul Rahem; Adistiar Prayoga (Journal of halal product and research (JPHR), 2020)
Coronavirus Disease (COVID-19) has become a global health problem since it was declared as a pandemic by the World Health Organization (WHO) as of March 11, 2020. Data from Johns Hopkins University (as of May 30, 2020) states that 5,930,096 cases confirmed in worldwide with a total fatality rate of 6 percent The prevention from COVID-19 transmission is to maintain the immunity. One way to maintain immunity is to maintain mental health by maintaining the religiosity factor. The development of technology and information causes information COVID-19 cases circulate quickly and massively. This condition can indirectly affect mental health and behavior change of affected entities. The student of the Faculty of Pharmacy, Maulana Malik Ibrahim State Islamic University (UIN Malang) is one of the affected entities of COVID-19. This study aims to determine the religiosity of the Faculty of Pharmacy students in facing COVID-19. The respondents of this study were 117 students of Pharmacy UIN Malang. The method used in this research is descriptive observational, with the aim to determine the religious practice or conditions of worship of students when facing an outbreak of COVID-19. The research instrument used in the form of a questionnaire related to the indicators and dimensions of the student religiosity that has been tested for validity and reliability.